2016
DOI: 10.1371/journal.pone.0157812
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Experience with a Polymer-Free Biolimus A9 Drug-Coated Stent in DES-Type Patients Who Are Poor Candidates for Prolonged Dual Anti-Platelet Therapy

Abstract: IntroductionProlonged dual anti-platelet therapy (DAPT) may cause excess bleeding in certain patients. The biolimus-A9 drug-coated stent (BA9-DCS) has a rapid drug-elution profile allowing shortened DAPT. Data were gathered on the early experience implanting this stent in drug-eluting stent eligible patients deemed to be at high risk of bleeding.Background and MethodsThe demographics, procedural data and clinical outcomes were gathered prospectively for 249 patients treated with a BA9-DCS stent at 2 UK centres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…In the LEADERS‐FREE trial (in which baseline anemia was a major inclusion criteria), use of a biolimus‐A9 coated stent without a polymer with only a 1‐month DAPT course demonstrated superior efficacy and safety over a BMS strategy . Subsequent clinical reports of the same technology along with several other trials of other emerging stent technologies are adding to the knowledge base of abbreviated DAPT in high‐risk groups . In future, abbreviated DAPT therapy in certain high‐risk groups combined with newer stent technologies might enable interventional cardiologists to undertake more effective revascularization in high risk groups such as the anemic, which may in turn improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the LEADERS‐FREE trial (in which baseline anemia was a major inclusion criteria), use of a biolimus‐A9 coated stent without a polymer with only a 1‐month DAPT course demonstrated superior efficacy and safety over a BMS strategy . Subsequent clinical reports of the same technology along with several other trials of other emerging stent technologies are adding to the knowledge base of abbreviated DAPT in high‐risk groups . In future, abbreviated DAPT therapy in certain high‐risk groups combined with newer stent technologies might enable interventional cardiologists to undertake more effective revascularization in high risk groups such as the anemic, which may in turn improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Following the removal of articles that did not meet our selection criteria (857) and duplicate items (613), 129 articles were deemed relevant for full‐text review. We further excluded 101 articles due to insufficient data, and 27 studies (24 RCTs, 3 OCS) qualified for the final analysis 8,10–36 . The PRISMA flow diagram is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, many studies have suggested that CKD has an independent influence on the incidence and prognosis of ischemic cardiac events [1,[20][21][22]. CKD is also posited to increase bleeding risk in patients requiring antiplatelet therapy because CKD is associated concurrently with increased bleeding tendency with platelet dysfunction and abnormal coagulation cascades [23,24]. Although previous study reported that patients with CKD tended to discontinue DAPT earlier than those without CKD [25], presence of renal insufficiency did not impact on the duration of DAPT in our study cohort.…”
Section: Discussionmentioning
confidence: 99%